Study of wave climate and port tranquility improvement around a mound causeway ore port in Hinadkaban Bay, Surigao del Norte - Giron, Julius Florenz B.
Assessment of port tranquility is essential as it is one of the factors that affect the operational capacity of the port. Rough wave climate at the port reduces the operating time of vessels and equipment, especially in the loading and unloading operation, that may be translated to unproductivity and losses. In this study, a wave climate analysis using REF/DIFI model is done to assess the port tranquility for incident prevailing wave conditions at an existing port used for mining operations situated along the Hinadkaban Bay, Surigao del Norte, CARAGA Region. Wave hindcasting, utilizing the Sverdrup-Munk-Bretschneider (SMB) method, is employed and results show that offshore waves coming from the east, northeast and east-northeast are frequent, with largest waves coming from east-northeast having deep water wave height of 1.76 m and period of 6.88 s. A criterion for safe loading conditions based on limiting wave heights is used and a wave height of 1.0 m is applied in the determination of adequacy and effectiveness of the existing layout for waves approaching at 0º angle and 0.8 m for wave approaching at 45º- 90º angle. From the results, it is concluded that. the waves coming from the northeast and east-northeast directions do not pass the criterion. A breakwater attached to the causeway is proposed and wave simulations show that wave heights are reduced to 0.5 m around the port. A re-orientation of the causeway is also proposed to minimize the angle between the incident wave and the vessel's long axis (bow to stern) that may reduce the movement of the vesse